Forty Canoes of Women: The Lives and Legacy of the Algonquian Women of 17th-Century New France - Campbell, Peter (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2022)
There has been an increasing tendency in recent decades to characterize North American Indigenous peoples as “people of the corn” living in permanent or semi-permanent settlements. This approach focuses on matrilineal, agricultural societies in which women play a central role in the economy and the organization of domestic life. Iroquoian women have been at the heart of this approach, while Algonquian women from patrilineal, hunter-gatherer societies remain in the shadows of the men who continue to be perceived as the main providers. In reality, on both the land and the water, the “nomadic” way of life of the people of the forest was anchored in the courage, strength, and endurance of Algonquian women providers.